Order in cellulosics: Historical review of crystal structure research on cellulose - Peter, Zugenmaier (Carbohydrate polymers, 2021)
The structure determination of cellulose represents a significant part in the history of polymer science. On one side, cellulose as a natural and renewable material has valuable physical properties which can be improved with detailed knowledge of the structure. On the other side, it is produced by nature as fibers, e.g. ramie, cotton etc., most suitable for structural studies by X-ray diffraction after their discovery in 1912 and was regarded by scientists as predestined for such an undertaking. The progress utilizing appropriate methods and models will be pursued in this investigation from the beginning of the structural research in 1913 till the proposal of realistic structures of cellulose in the 1970s. Different basic units of the crystal structure are discussed. Many structural models for native cellulose have been suggested over times with parallel or antiparallel running chains in the fibers and supported or abandoned. In this historical review on order in cellulosics, the crystal structure research throughout the times will be critically evaluated and the improvements in experiments and methods discussed. This subject is not restricted to cellulose rather can be extended to further polymer fibers.